Pengaruh Pendidikan Kesehatan Melalui Media Video Animasi Terhadap Kemampuan Toilet Training Anak Usia 3-4 Tahun - Alfiana, Eva Alfiana; Wahyuni, Tavip Dwi; Marcelina, Sheilla Tania; Bahari, Kissa (Poltekkes Kemenkes Malang, 2024)
Toilet training can be used to train children to control urination and defecation independently. Teaching toilet training requires a method that is easy for children to understand. You do this through the use of video media because it can display messages. The purpose of the study was to determine the effect of health education through animated video media on toilet training skills in children aged 3-4 years in PAUD. The research design is pre-experiment with one group design, pretest, posttest design without control group. The sampling technique uses total sampling on all children aged 3-4 years. Data collection using questionnaires analyzed with the Wilcoxon test. The results showed that before the intervention, the mean value was 11.83, meaning that the child did not succeed in toilet training with a minimum value of 5 and a maximum value of 14. Then, after the intervention, the ability of toilet training increased with a mean value of 26.13 which means that the child succeeded with a minimum score of 21 and a maximum value of 28. The results of the Wilcoxon test obtained a p-value of 0.000 < ? = 0.05 showing that there was an influence of health education through animated video media on the ability of toilet training in children aged 3-4 years at the Ade Irma Suryani PAUD Post. Animated video media is expected to be used as an alternative to improve children's toilet training